2015
DOI: 10.1111/epi.12832
|View full text |Cite
|
Sign up to set email alerts
|

Children with epilepsy and anxiety: Subcortical and cortical differences

Abstract: Summary Objective Using a hypothesis driven approach, subcortical and cortical regions implicated in anxiety disorders in the general population were examined in children with recent-onset epilepsy with versus without anxiety compared to controls. This study reports frequency of anxiety disorders while examining familial, clinical and demographic variables associated with anxiety in children with epilepsy. Method Participants included 88 children with epilepsy aged 8–18 years; 25 with a current anxiety diso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 37 publications
2
24
0
1
Order By: Relevance
“…In our study, however, the group differences of cortical thickness asymmetries remained highly significant when we excluded the valproate users. Another confounding factor could be epilepsy-associated anxiety: a recent study of 25 children with recent-onset epilepsy and anxiety disorder demonstrated thinning in bilateral orbital frontal and prefrontal cortex [31]. Although we did not have detailed neuropsychology data on anxiety, only one patient had clinically diagnosed depression in our cohort.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, however, the group differences of cortical thickness asymmetries remained highly significant when we excluded the valproate users. Another confounding factor could be epilepsy-associated anxiety: a recent study of 25 children with recent-onset epilepsy and anxiety disorder demonstrated thinning in bilateral orbital frontal and prefrontal cortex [31]. Although we did not have detailed neuropsychology data on anxiety, only one patient had clinically diagnosed depression in our cohort.…”
Section: Discussionmentioning
confidence: 99%
“…Akin to neuroimaging findings in patients with epilepsy and ID, patients with epilepsy and anxiety demonstrate alterations in volumes of gray matter structures. In children with epilepsy and an anxiety disorder, the volume of the amygdala was increased and the thickness of orbitofrontal cortices was reduced . Widespread changes in gray matter are also observed in children with epilepsy and ADHD .…”
Section: Imaging Biomarkers Of Comorbiditiesmentioning
confidence: 99%
“…Severity of depression post mild TBI was correlated with reduced volume in the anterior cingulate, temporal lobe and insula. Jones et al (2015) found larger volume of the amygdala as derived from FreeSurfer to be associated with increased levels of anxiety in children with epilepsy. Reduced OFC was also related to higher levels of reported anxiety which would be consistent with poorer emotional control as reported in the Krueger et al (2011) study previously discussed.…”
Section: Contemporary Examples Of Structural Neuroimaging Findings Inmentioning
confidence: 83%